Effect of pig breeding scale on manure resource utilization-The moderating effect based on technology cognition - Jiangqi Sun; Zongzheng Liu; Juan Ai; Zhaojiu Chen (PLoS ONE, 2025)
The utilization of manure resources is an important measure to promote the development of agricultural green low-carbon cycle and solve the challenges associated with the current large-scale development of the livestock and poultry breeding industry. Based on the survey data of pig farmers in Qingdao, Shandong Province, China, this paper constructs a theoretical analysis framework of pig breeding scale and technical cognition on the utilization behavior of livestock and poultry manure resources of pig farmers. The binary Logit model and the moderating effect model are used to deeply explore the scale effect of breeding scale on the utilization behavior of pig farmers’ manure resources, and the moderating effect of technical cognition on the influence of breeding scale on the utilization behavior of manure resources. First, at the present stage, pig farmers show certain differences in the resource utilization of manure. Due to the differences in the personal characteristics, family characteristics, and breeding characteristics of pig farmers, the influencing factors of resource utilization of pig farmers of different scales are different; Second, the scale of pig breeding has a significant positive promoting effect on the resource utilization of manure, increasing the probability of pig farmers to treat manure, guiding retail and small-scale farmers to moderately expand the scale of breeding, gradually moving to large-scale breeding, realizing centralized management and resource utilization of manure, and reducing the unit cost of manure treatment. Third, technical ease of use has a positive regulatory effect on pig breeding scale and manure resource utilization behavior. When pig farmers perceive that the technology of manure resource utilization is easy to use, they will increase the probability of participating in the resource utilization of manure, reduce the environmental pollution caused by improper disposal of manure, and promote the low-carbon and circular development of livestock and poultry industry. Based on the above findings, this paper aims to provide practical enlightenment for policy makers and researchers to strengthen the environmental governance and sustainable development of livestock industry.